Kebijakan Internasional Dan Regulasi Penanganan Sampah Antariksa (Space Debris) - Ana Ilmadan Sari; Heni Ananta; Oksya Wina Azzahrah; Rego Bangkito (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Space has developed into a global strategic infrastructure supporting various aspects of modern life, such as communications, navigation, Earth observation, and disaster mitigation. The increasing frequency of satellite launches, particularly with the involvement of commercial actors, has triggered a significant increase in space debris, threatening the safety of satellite operations and the sustainable use of space. This study aims to analyze current international policies and international space law regulations addressing the issue of space debris and assess their effectiveness in ensuring the sustainability of space. The research method used is normative legal research, using a legislative and conceptual approach to the international space legal regime. The results indicate that international legal regulations regarding space debris are still partial and have not been comprehensively regulated in a single, binding international legal instrument. The existing legal regime relies on general principles of space law and is supported by soft law instruments that lack legal binding force. Consequently, the effectiveness of international regulations in preventing the increase in space debris and ensuring the sustainable use of space remains limited.